Compressive strength of masonry grout containing high amounts of class F fly ash and ground granulated blast furnace slag. (30th September 2015) - Fonseca, Fernando S.; Godfrey, Robert C.; Siggard, Kurt
Highlights: Masonry grouts with fly ash and slag replacing high amounts of cement is discussed. A model is presented that describes the strength evolution of masonry grouts. Grouts with up to 55% ash and 85% ash–slag can be treated as conventional grout. Ternary mixes achieve higher ultimate strengths than binary and cement only mixes. Results show a viable alternative to make masonry more economical and sustainable. Abstract: A large testing program was devised to determine the compressive strength of masonry grouts made with various combinations of class F fly ash and ground granulated blast furnace slag to replace high amounts of Portland cement. In a first phase, mixes were proportioned by volume and batched with 0, 20, 30, 40, 50, and 60 percent Portland cement replacement; specimens were cured in a dry and wet environment. The objective of the first phase was to determine the viability of and the methodology for the overall project. In the second phase, mixes were proportioned by weight, the more common practice in the United States, and batched with 0, 20, 30, 40, 45, 50, 55, 60 and 65 percent Portland cement replacement. Specimens in the second phase were cured in a wet environment only. In the first and second phases, Portland cement was replaced only by fly ash. In the third phase, mixes were proportioned also by weight and batched with 0, 50, 60, 65, 70, 75, 80, and 85 percent Portland cement replacement. In the third phase, Portland cement was replaced by combinations of fly ash and ground granulated blast furnace slag; however, the fly ash content was maintained constant at 25 percent. Specimens in the third phase were also cured in a wet environment only. Specimens were typically tested at 14, 28, 42, 56, and 90 days; in Phase I specimens were also tested at 7 days but not at 90 days. Three specimens were tested for each replacement rate, age, and curing conditions. Several mixes developed satisfactory strength, i.e., the mixes achieved the ASTM specified minimum compressive strength of 13.8 MPa at 28 days. The results show that mixes with up to 55 percent fly ash and 85 percent fly ash-ground granulated blast furnace slag substitutions reached the minimum compressive strength required at 28 days. Mixes with up to 60 and 65 percent fly ash achieved the minimum compressive strength of 13.8 MPa in 44 and 54 days, respectively.